Java, the garden of the East - Scidmore, Eliza Ruhamah (The Century Co., 1987)
This late-nineteenth century travel book, written by an American visitor, has been described as a 'seminal work', opening as it did to Western eyes the glories, curiosities and mysteries of Java, an island little known in the Western world at that period. With feminine intrepidity, the author provides for us unique vignettes of various aspects of Javanese and Dutch- Javanese life in the heyday of colonial rule.